(untitled) (Italian Review of Legal History, 2015)
The essay deepen the study of fiftheenth-century tractatus de testibus, started with Tindaro Alfani (RSDI 2007 but 2008), by comparing the works by Nello from San Gimignano and Alberico Maletta. Analogies and differences between the texts’ frame and the doctrinal contents are analyzed. The article is part of a research which aims to demonstrate the role as laboratory of the fiftheenth-century tractatus as to the sixteenth century results: the fiftheenth-century jurists tested new languages and frames which made possible the synthesis of the contents of the Commentaria.